Rekayasa Perangkat Lunak Sistem Pendukung Keputusan Pemberian Kredit (Studi Kasus pada BPR Argo Dana Semarang) - Hersatoto Listiyono; Sunardi .; Teguh Khristianto (Universitas Stikubank, 2011)
Decision support system of credit giving is a computer-based information system that can be used as a tool for manager of the credit department to decide received whether or not the loan application that submitted by customers. In the decision support system of credit giving uses principles of assessment called the 5 C. The 5 C are character, capacity, capital, collateral, dan condition. Principles of the 5 C will be taken for credit giving consideration. While preference for the weighting of criteria using Analytical Hierarchy Process. Overall, the existing process on the decision support system of credit giving is manager assigned the criteria, sub criteria, sub-sub criteria and the score. Then manager give preference of criteria to generate criteria weights. The data has been inputted by manager is used by staff of credit department to perform the assessment so that can be produced a credit decision is received or rejected.